Aransemen Musik Sekolah Dengan Judul “Rumah Kita” - Lily Juwita; Erfan Erfan; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2019)
This artwork aims to express an idea that is poured through music performances in the form of music arrangement. In this song, arranger worked in the form of school music arrangement. The band Combo at SMK N 7 Padang corresponds to the ability of ensembles studied by students. Here arranger arranged song our house is played with some vocal music accompaniment, keyboard, bass, guitar, drums. The arransemen in this piece of music contains lyrics that explain that as bad and cruel as any of this country we must remain grateful and devoted to the homeland. By building new things through some development techniques such as reps, modulation, Augmentsi, diminution, arpeggio and various other techniques without changing the essence of the song of our house. Arransemen song popularized by one of the Indonesian rock band Goodbles with the title song